Sulfonated zinc phthalocyanine coating as an efficient and ecofriendly corrosion inhibitor for copper surfaces: an in silico led design and its experimental validation - Dekshinamoorthy, Amuthan; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Khatri, Praveen K.; Jain, Suman Lata; Ray, Anjan; Vijayaraghavan, Saranyan (Langmuir, 2023)
The current study highlights the successful integration of an in silico design with experimental validation to create a highly effective corrosion inhibitor for copper (Cu) surfaces. The synthesized sulfonated zinc phthalocyanine (Zn-Pc) is electrochemically characterized and demonstrates an impressive 97% inhibition efficiency, comparable to the widely used industrial corrosion inhibitor, BTA, for Cu surfaces. The corrosion inhibition is comprehensively analyzed through potentiodynamic polarization and impedance spectroscopy techniques, supported by their respective equivalent circuits. Furthermore, the sample undergoes thorough characterization using scanning electron microscopy, energy-dispersive X-ray analysis, X-ray photoelectron spectroscopy, contact angle measurements, and atomic force microscopy. Density functional theory calculations reveal that sulfonated Zn-Pc exhibits the highest interaction energy, underscoring its exceptional inhibition properties. These results open possibilities for utilizing computational methods to design and optimize corrosion inhibitors for protection of Cu surfaces.